2021
DOI: 10.1098/rspb.2021.0548
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic wasps do not lack lipogenesis

Abstract: Fatty acids are crucial primary metabolites for virtually all creatures on earth. Most organisms thus do not rely exclusively on a nutritional supply containing fatty acids, but have the ability to synthesize fatty acids and triacylglycerides de novo from carbohydrates in a process called lipogenesis. The ubiquity of lipogenesis has been questioned by a series of studies reporting that many parasitic wasps (parasitoids) do not accumulate lipid mass despite having unlimited access to sugar. This has been interp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…Thus, we posit that it is important to consider the overall impact of lipid synthesis and accumulation. The very low amounts of fatty acid synthesis detected by Ruther et al (2021) are unlikely to play a critical role as an energy source or as an anabolic substrate for egg production, compared to the wasps' physiological requirements. In fact, a similar finding was proposed almost two decades ago by Giron and Casas (2003) who also found trace amounts of incorporation of glucose into fatty acids using radioactive labels, and concluded that there was no substantial lipogenesis occurring.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Thus, we posit that it is important to consider the overall impact of lipid synthesis and accumulation. The very low amounts of fatty acid synthesis detected by Ruther et al (2021) are unlikely to play a critical role as an energy source or as an anabolic substrate for egg production, compared to the wasps' physiological requirements. In fact, a similar finding was proposed almost two decades ago by Giron and Casas (2003) who also found trace amounts of incorporation of glucose into fatty acids using radioactive labels, and concluded that there was no substantial lipogenesis occurring.…”
mentioning
confidence: 96%
“…In a strictly chemical sense, the answer is no, but from the perspective of the accumulation of lipid stores for adult energetics and reproduction, we believe the answer is yes. Rather than a core conceptual disagreement between Ruther et al (2021) and us, this seems to be a semantic problem that we hope will be ameliorated by the use of term "lack of lipid accumulation" in future work.…”
mentioning
confidence: 97%
See 3 more Smart Citations